Investigation of the performance of a MicroMegas detector suitable for neutron-induced fission cross-section measurements - Diakaki, M.; Kokkoris, M.; Kyrtsos, A.; Skordis, E.; Vlastou, R.; Nicolis, N. G.; Lagoyannis, A.; Andriamonje, S.; Berthoumieux, E. (HNPS Advances in Nuclear Physics, 2013)
The performance of a state-of-the-art MicroMegas detector, suitable for neutron- induced fission cross-section measurements has been examined. Special emphasis was put on the study of the gain and the resolution function.